Sustainable Runggu Strengthening Model: Communal Intellectual Property Protection in Ecotourism Puncak 2000 Siosar, Karo Regency - Amelia Anggriany Siswoyo; Palacheta Subies Subianto (Journal of Law, Politic and Humanities, 2024)
Runggu is a model of local wisdom of the Karo indigenous community that has an important role in the kinship system, communication and deliberation to make a decision in the Karo indigenous community. Runggu is a collection of "human living treasure" that can protect and preserve the communal intellectual property of the Karo people. Puncak 2000 Siosar has a lot of potential that can be explored by Runggu to be inventoried and recorded as communal intellectual property. The lack of communal intellectual property literacy, communal intellectual property commercialization literacy and customary communal literacy causes communal intellectual property to not be utilized economically for the development of ecotourism of the Karo community in Puncak 2000 Siosar. Even though communal intellectual property is commercialized, indigenous peoples will get fair and equitable benefits sharing that has the potential to improve the welfare of local communities. However, it takes synergy and active collaboration from various relevant stakeholders, especially from the Runggu Karo community in the Puncak 2000 Siosar Ecotourism area to make Karo communal intellectual property a regional superior product. The data analysis technique used in this research is quantitative data analysis technique using statistical methods using SmartPLS software version 4.0. The conclusion of this research is that increasing indigenous communal literacy in the context of communal intellectual property has a double effect. On the one hand, it encourages indigenous peoples to better appreciate and preserve their cultural heritage. On the other hand, this literacy also opens up opportunities for indigenous peoples to utilize their intellectual property commercially.